In Silico Study Green Tea Compounds (Camellia sinensis) as Antibacterial Candidates against Streptococcus mutans (ALKIMIA : Jurnal Ilmu Kimia dan Terapan, 2025)
Streptococcus mutans is the main bacterium that causes dental caries. This bacterium allows the metabolism of sucrose into lactic acid. This results in a decrease in pH around the teeth and facilitates the dissolution of calcium phosphate from tooth enamel, which causes tooth decay. Generally, caries treatment can be done by giving antibiotics, but over time antibiotics have caused resistance. One of the efforts to treat caries is the use of natural ingredients that have antibacterial properties. Green tea (Camellia sinensis) is a natural ingredient that has bioactive compounds that are antibacterial. This study aims to determine the potential of active compounds of green tea leaves against Streptococcus mutans bacteria in silico. The in silico study research conducted was molecular docking with 3AIC targets, prediction of physicochemical properties, prediction of toxicity and prediction of biological activity. Based on the results, it is known that the Epicatechingallate compound provides better inhibition than other compounds and also the comparator ligand in the form of positive control chlorhexidine and negative control chloramphenicol as indicated by the binding affinity value of -9.5 kcal/mol. The predicted physicochemical properties showed that Epicatechingallate compound fulfills Lipinski's Law of Five. Based on LD50 toxicity class, catechin-derived compounds belong to class 4 and 6 and based on biological activity catechin-derived compounds are antibacterial. In conclusion, it can be seen that Epicatechingallate compounds can be developed as antibacterial candidates against Streptococcus mutans.